Genome-Wide Identification of Evolutionarily Conserved Alternative Splicing Events in Flowering Plants - Chamala, Srikar; Feng, Guanqiao; Chavarro, Carolina; Barbazuk, W. Brad (Frontiers in Bioengineering and Biotechnology, 2015)
Alternative splicing (AS) plays important roles in many plant functions, but its conservation across the plant kingdom is not known. We describe a methodology to identify AS events and identify conserved AS events across large phylogenetic distances using RNA-Seq datasets. We applied this methodology to transcriptome data from nine angiosperms including Amborella, the single sister species to all other extant flowering plants. AS events within 40 – 70% of the expressed multi-exonic genes per species were found, 27,120 of which are conserved among two or more of the taxa studied. While many events are species specific, many others are shared across long evolutionary distances suggesting they have functional significance. Conservation of AS event data provides an estimate of the number of ancestral AS events present at each node of the tree representing the 9 species studied. Furthermore, the presence or absence of AS isoforms between species with different whole genome duplication (WGD) histories provides the opportunity to examine the impact of WDG on AS potential. Examining AS in gene families identifies those with high rates of AS, and conservation can distinguish ancient events vs. recent or species specific adaptations. The MADS-box and SR protein families are found to represent families with low and high occurances of AS, respectively, yet their AS events were likely present in the MRCA of angiosperms.